Analisis Spesifisitas Terhadap Sensor NPK - Ivan Lionel; Abdul Ro'uf; Bakhtiar Alldino (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2023)
Insufficient use of fertilizers results in non-optimal plant growth, while excessive use is wasteful and results in pollution. Sensor usage is one method for measuring the nutrient content in the soil so that the fertilization process can be carried out precisely. Accuracy, precision, and error are commonly used in analyzing sensor quality. But for chemical measurements, the specificity also needs to be analyzed. This is because the soil contains various types of nutrients, so it is necessary to know whether the readings from the sensor only come from the desired nutrients or the others. In this writing, the elements measured were N, P, and K which are nutrients needed by plants in large quantities. The sensors were tested using compounds containing N, P, or/and K elements and NPK fertilizers with different NPK ratios. Results of this study prove that the sensor is not specific as the readings are known to use the electroconductivity method as proved by the regression results between the two variables which have RÂ² â‰ˆ 1 correlation. In addition, the sensor also produces readings for elements/compounds that should not be read and cannot distinguish the ratio of types of compound NPK fertilizer with different types.